Continuation of Dating It Safe: A Longitudinal Study on Teen Dating Violence, Houston, Texas, 2010-2018 - Temple, Jeff R. ([Verlag nicht ermittelbar], 2022)
Dating It Safe is a longitudinal cohort study of 1,042 youth in southeast Texas. Primarily freshmen high school students were recruited and assessed in the spring of 2010. Follow-up waves were collected annually each spring from 2011 through 2017 (Waves 2-8). The primary aims of this research study were to examine the: longitudinal association between the three different forms of teen dating violence (TDV; i.e., physical violence, psychological abuse, and sexual aggression), and risk and protective factors of TDV perpetration and victimization.